Further Results on Ph-supermagic Trees - Tita Khalis Maryati; Otong Suhyanto; Fawwaz Fakhrurrozi Hadiputra ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2023)
Let $G$ be a simple, finite, and undirected graph. An $H$-supermagic labeling is a bijective map $f : V(G) \cup E(G) → \{1,2,…,|V(G)|+|E(G)|\}$ in which $f(V) = \{1,2,…,|V(G)|\}$ and there exists an integer $m$ such that $w(H') = \sum_{v \in V(H')} f(v) + \sum_{e \in E(H')} f(e) = m$, for every subgraph $H' \cong H$ in $G$. In this paper, we determine some classes of trees which have $P_h$-supermagic labeling.